Return Migration to India: Decision‐Making among Academic Engineers and Scientists. (8th June 2016) - Sabharwal, Meghna; Varma, Roli
Abstract: The decision‐making process among migrants, whether to leave their country of birth for a foreign country or deciding to return to their native country is complex and laden with challenges. This article seeks to understand the decision‐making process by which immigrant engineers and scientists select to return to India after study and work in the United States. It is based on in‐depth interviews conducted with 54 returned engineers and scientists. Results indicate that the decision to return is anything but a linear process as highlighted in rational choice theory. Prospect and planned behaviour theories are better positioned to explain the decision‐making process among returned migrant engineers and scientists.